Health-Seeking Behavior of People in Indonesia: A Narrative Review - Anna Wahyuni Widayanti; James A. Green; Susan Heydon; Pauline Norris (Springer, 2020)
This review aims to locate existing studies on health-seeking behavior of people in Indonesia, identify gaps, and highlight important findings. Articles were retrieved from Medline, Scopus, Web of Science, Academic Search Complete (via Ebsco), and ProQuest with a number of key words and various combinations. Articles from Indonesian journals were also searched for with Google Scholar. A total of 56 articles from peer-reviewed journal databases and 19 articles from Indonesian journals were reviewed. Quantitative designs were applied more frequently than qualitative, and mixed methods designs were used in some studies. The majority gathered retrospective information about people's behaviors. Communicable diseases and maternity care were the most frequently studied conditions, in contrast to noncommunicable diseases. In terms of geographical distribution, most research was conducted on Java island, with very few in outside Java. Important findings are a model of Indonesian care-seeking pathways, an understanding of determinants of people's care choices, and the role of sociocultural beliefs. The findings from this narrative review provide insight to what and how Indonesians make decisions to manage their illness and why. This makes an important contribution to understanding the problem of underutilization of medical services despite the government's extensive efforts to improve accessibility.